Content Analysis Of The Al-Arabiyyah Lil ‘Alam Educational Series Based On Gardner's Theory Of Multiple Intelligences - Pasandi, Faezeh; Hosein Abadi, Safoura Ghadami (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
According to modern educational theories, organized intelligences are key to effective learning and practical second language instruction. Howard Gardner's